(untitled) (BIBECHANA, 2010)
The large asymmetry observed in free energy of mixing of HgK liquid alloy is discussed on basis of Flory’s model. The concentration dependence of the free energy of mixing and activity of mercury has got special attention in the discussion. Key words: liquid alloy; Flory’s model; Free energy of mixing; activity. DOI: 10.3126/bibechana.v6i0.3934 BIBECHANA Vol. 6, March 2010 pp.18-21